Impact of ocean acidification on coral reef ecosystem services and marine biodiversity - Boymuradov, Shukhrat; Fallah, Mohammed; Khayrullo Ugli, Jumaboev Nurillo; M.A, Bruno; Dewangan, Tripti (International Journal of Aquatic Research and Environmental Studies, 2025)
Anthropogenic carbon dioxide emissions are a cause of ocean acidification (OA), an acute and rapidly growing threat to global coral reef ecology and the services they provide to the world. The study will examine the multifaceted effects of OA on the biophysical structure of coral reefs and the consequent reduction in associated marine biodiversity. The rising acidity of seawater disrupts the calcification process in corals and other animals that build CaCO3 shells, thereby reducing reef health and further contributing to its deterioration and subsequent dissolution. These modulations reduce the reef’s ability to provide critical ecosystem services, including coastal protection, support for fisheries, and tourism earnings. In addition, OA acts independently and in combination with other stressors, such as warming and local pollution, to increase the intensity of habitat degradation, thereby influencing the survival and performance of the majority of marine animals. The study employs a simplified literature review and a single Socio-Ecological Economic Assessment Framework (SEEAF) to simulate the quantifiable and qualitative reductions in key ecosystem indicators. We specifically address the economic impacts on coasts that depend on reef fisheries and comment on potential solutions to mitigate them. The findings highlight the necessity of international and local carbon-cutting efforts to preserve these precious marine environments. The research is baseline research on the significance of OA to the policy makers, be it ecologically or economically, to ensure the future health of the reefs.